Neuromuscular Interfacing for Advancing Kinesthetic and Teleoperated Programming by Demonstration of Collaborative Robots - Meattini, Roberto; Ameri, Armando; Bernardini, Alessandra; Gonzalez-Huarte, Javier; Ibarguren, Aitor; Melchiorri, Claudio; Palli, Gianluca (IEEE transactions on haptics, 2025)
This study addresses the challenges of Programming by Demonstration (PbD) in the context of collaborative robots, focusing on the need to provide additional degrees of programming without hindering the user's ability to demonstrate trajectories. The study proposes the use of a wearable human-robot interface based on surface Electromyography (sEMG) to measure the forearm's muscle co-contraction level, enabling additional programming inputs through hand stiffening level modulations without interfering with voluntary movements. Vibrotactile feedback enhances the operator's understanding of the additional programming inputs during PbD tasks. The proposed approach is demonstrated through experiments involving a collaborative robot performing an industrial wiring task. The results showcase the effectiveness and intuitiveness of the interface, allowing simultaneous programming of robot compliance and gripper grasping. The framework, applicable to both teleoperation and kinesthetic teaching, demonstrated effectively in an industrial wiring task with a 100% success rate over the group of subjects. Furthermore, the presence of vibortactile feedback showed an average decrease of programming errors of 33%, and statistical analyses confirmed the subjects' ability to correctly modulate co-contraction levels. This innovative framework augments programming by demonstration by integrating neuromuscular interfacing and introducing structured programming logics, providing an intuitive human-robot interaction for programming both gripper and compliance in teleoperation and kinesthetic teaching.